IMPLEMENTASI PROGRAM BEDAH DESA SEBAGAI UPAYA PENGENTASAN KEMISKINAN DI KABUPATEN KLUNGKUNG (STUDI KASUS DI DESA SELAT, KECAMATAN KLUNGKUNG) - Damayanthi, Ida Ayu Sri; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
Bedah Desa is an innovation program created by the Klungkung Regency Government which aims to inventory problems in the village also to explore the potential of each village in Klungkung Regency. This research uses descriptive qualitative research methods with data collection techniques such as observation, interviews, and documentation. The results of this research applying the policy implementation model approach according to Van Meter and Van Horn through six indicators, namely aims and standards policy, resources, characteristics of implementing agents, communication between organizations, disposition of implementing agents, social, economic, and political environment. Based on this analysis, it shows that Bedah Desa Program implementation in Klungkung Regency has not been able to run optimally, because there are still several problems such as, there is no systematic program implementation schedule, the lack of completion targets and supervision related to follow-up the assistance provided. Keywords: Policy Implementation, Bedah Desa Program, Poverty, Klungkung Regency